ANALISIS HUBUNGAN WAKTU TEMPUH DENGAN DERAJAT KEJENUHAN RUAS JALAN PERKOTAAN (Studi Kasus Kota Semarang) - Anindyawati Nina, Nina (Department of Civil Engineering, 2008)
This research discusses the relation between Travel Time and Degree of Saturation for the urban roadlinks, especially for the city of Semarang, by using regression method which Travel Time as apolynomial function of Degree of Saturation.Siliwangi Street and Soekarno-Hatta Street are selected as the sample for arterial road, ThamrinStreet and Supriyadi Street as the sample for collector road, and Lampersari Street and KsatrianStreet as the sample for local road. The research found the general formula for Travel Time andDegree of Saturation relationship for the urban road links as : W = wl [ 1 + a ( DS )4 ] , where the W isthe travel time, the wl is the travel time at the free flow and the DS is the degree of saturation.It is also found that the arterial road wl = 6,5 – 6,75 second and a = 0,15 – 0,4 , collector road giveswl = 8,25 – 8,9 second and a = 0,4 – 0,6 and local road, gives wl = 9,62 – 11,93 second and a = 0,3 –0,4.The research has shown that the travel time and degree of saturation relation model for arterial roadwas exactly similar to the Indonesian Highway Capacity Manual (IHCM ), 1997 standard, but for bothof collector road and local road were not in the same condition. It means that in this case theIndonesian Highway Capacity Manual ( IHCM ), 1997 standard was only able to be used for arterialroad. It is not recommended to use the Indonesian Highway Capacity Manual ( IHCM ), 1997standard for collector road and local road.